Annual Plan 2006-07 (Sectoral Plans) Volume-II Government of Nagaland - Planning Commission (Planning Commission, 2006)
The Department of Science & Technology in the State has its areas of activities which broadly covers the following areas I) S & T popularization II) Research & Development projects on both S & T sector and Ecology & Environment III) New & viable projects on Non-conventional Sources of Energy and IV) Bio-technology project. All the above activities are being done in association with the various Central Ministries of GOI and other research institutions. During 2006-07 the department proposes to take up the following activities.
Government of Nagaland, Planning and Co-ordination Department